Development and validation of a rapid psychosocial well-being screening tool in patients with metastatic breast cancer - Bhumipat Thanasansomboon; Songphan Choemprayong; Napa Parinyanitikul; Uthai Tanlamai; Manika Wisessathorn; Yupin Patarapongsant (Elsevier, 2022)
Objective: The aim of this study was to develop and validate a rapid psychosocial well-being screening tool for metastatic breast cancer patients (MBC-PsySoc-Well-being). Methods: Applying a mixed method approach, the study was conducted in two phases. Phase 1, a focus group method was employed for item development, and three focus group sessions were conducted, with patients, caregivers, and medical professionals, respectively. Phase 2, validity and reliability testing were performed. Five experts reviewed items for content validity. Construct validity, criterion-related validity, internal consistency, and test-retest reliability were conducted among a sample of 53 patients with metastatic breast cancer. Results: Six themes were qualitatively analyzed based on focus group participants' responses. Eight items were then developed based on these themes. The index of Item-Objective Congruence scored by the experts ranged from 0.6 to 1.0. An exploratory factor analysis yielded three factors: Being curious and active in information seeking, Enthusiasm to return to a normal life, and Adjusting to positive lifestyle. The total scores of MBC-PsySoc-Well-being and the European Organization for Research and Treatment of Cancer's Quality of Life Core Questionnaire (EORTC QLQ-C30) were moderately correlated (r = 0.404, P = 0.003). Cronbach's α coefficient of the overall scale was 0.686. Pearson correlation coefficients of items between two tests within 14-day ranged from 0.410 to 0.673. Conclusion: This study represents an initiative to develop a rapid psychosocial well-being screening tool for patients with metastatic breast cancer. The results from validity and reliability testing indicate that the scale is moderately suitable for application to patients with metastatic breast cancer. However, a larger scale study should be further administered to confirm the validity and reliability of the measurement.